ENT300 Fundamental of Entrepreneurship. Business Plan : Mockingjay Futsal Centre / Muhd. Haniz Azahari Muhamad Suhaili... [et al.] - Muhamad Suhaili, Muhd. Haniz Azahari; Hamdani, Illyas Azmeer; Haji Sulaiman, Khalid; Shafie, Muhd. Afifuddin; Joisin, Jasper (2015)
Preparing and providing fusal court facilities (futsal arena, futsal ball, court lightning and etc.). Provide good service and comfort for customers to enjoy and have fun while playing futsal. Specialty based on the theme of the business; comfort, vintage and quality.